Perspective of Developer, Buyer, Financier and Equity Participants in Real Estate Project Development Process in India: An important constituent of Construction Industry - Singh, Alok (International Journal of Management Excellence (ISSN: 2292-1648), 2017)
The real estate project development is an important constituent of construction industry. The other important constituent of construction industry is infrastructure development. The construction industry drives and impacts many other industries and has a substantial multiplier effect on various sectors and hence on economic output as well as on employment scenarios. This article discusses multiplier effect of construction industry on few of the important economic indicators and further focuses on real estate project development process. The real estate project development process starts from land acquisition to sales and marketing. The internal stakeholders in real estate project development process are real estate developers, real estate buyers and the real estate financers. The paper discusses alternatives for real estate developers, the opportunistic schemes for real estate buyers, and the role of portfolio of financing agencies as well as the role of multitudes of equity participants. It also describes about the regulatory institutions active in real estate project development and promotion process. The real estate projects are developed by organized real estate project developer as well as by unorganized real estate project developers or local builders. This article contributes regarding the challenges and opportunities among the real estate buyers, real estate developers, portfolio of financial schemes offered by real estate financers and the opportunities for real estate equity participants.